Two new species of Sphaeronemoura (Plecoptera: Nemouridae) from Oriental China - Li, Weihai; Yang, Juan; Yang, Ding (Zootaxa, 2016)
Two new species of the genus Sphaeronemoura of the stonefly family Nemouridae, S. asymmetria sp. n. from Guizhou Province and S. hainana sp. n. from Hainan Province, respectively, are described from China. These findings represent the first record of the genus from these two provinces. Their relationships with other species from adjacent regions are discussed. With the new species described herein, 16 species of Sphaeronemoura are now known.